Decoding myofibroblast origins in human kidney fibrosis - Kuppe, Christoph; Ibrahim, Mahmoud M.; Kranz, Jennifer; Zhang, Xiaoting; Ziegler, Susanne; Perales-Patón, Javier; Jansen, Jitske; Reimer, Katharina C.; Smith, James R.; Dobie, Ross; Wilson-Kanamori, John R.; Halder, Maurice; et al. (Nature, 2021)
Kidney fibrosis is the hallmark of chronic kidney disease progression; however, at present no antifibrotic therapies exist
Gesehen am 02.05.2024
Online veröffentlicht: 11 November 2020